Mental health, social inclusion and the development of vocational services in the NHS – what can be learnt?. Issue 2 (2nd July 2019) - Bertram, Mark
Abstract : Purpose: The purpose of this paper is to describe the learning from a historical NHS vocational service development that focused on: mental health, employment and social inclusion – in an inner city area – involving service users, staff and commissioners. Design/methodology/approach: It is a descriptive case study. A range of historical documents was content analysed and described through a first-person narrative: service user consultations, service specifications, audit records, outcome frameworks, internal service evaluations and published literature. Findings: When vocational NHS service developments are grounded in what service users say helps them (person-centred, networked and co-ordinated approaches) the evidence indicates people can achieve their vocational goals. Research limitations/implications: The range of documents described is factual, although the learning insights from some of the service developments are based on personal judgements. The author was the responsible manager – personal bias is high. There is not enough robust evidence to warrant generalisation. Practical implications: When employment and social inclusion are prioritised, as core business in NHS, outcomes and health impact can increase. Greater detail is needed from healthcare policy makers – focusing on who exactly should undertake this work and what the key commissioning social inclusion performance indicators are. Originality/value: The bulk of literature on employment support focuses on promoting evidence from one model: individual placement and support. Evidence here indicates a broader range of activity (education, training and volunteering) can have value and health impact.